The manifestation of Cadre deployment in selected SOWETO public schools: Voices of teachers in despair - Mkhomi, Moses Sipho (Technium Social Sciences Journal, 2025)
Cadre deployment in South African Public Schools is steadily becoming a norm than an exception and breeds protracted intergroup conflicts as promotional posts are reserved for politically aligned teacher union members. These conflicts affect the quality of teaching and learning, as the focus of the teachers move from the primary purpose of teaching to contestation for senior posts. This paper uses Intergroup Conflict Theory and Dynamic Conflict Theory as lenses to explore and explain the intergroup conflicts as manifested in South African Public Schools because of sustained application of cadre deployment. The interpretivism paradigm was employed in this study. Qualitative research approach was used to collect data from 6 teachers, in 3 selected SOWETO schools. The findings of this study revealed that, despite the SADTU’s denial of involvement in pursing cadre deployment, this practice is a norm in the selected schools and experienced and qualified teachers who are non-SADTU members are overlooked for promotional posts. This paper, therefore, recommends for the review of minimum promotional requirements in public schools, considering experience and qualifications in the selection and recruitment of teachers to senior posts.